2014
DOI: 10.1016/j.gene.2014.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Integration of gene expression data with network-based analysis to identify signaling and metabolic pathways regulated during the development of osteoarthritis

Abstract: Osteoarthritis (OA) is characterized by remodeling and degradation of joint tissues. Microarray studies have led to a better understanding of the molecular changes that occur in tissues affected by conditions such as OA; however, such analyses are limited to the identification of a list of genes with altered transcript expression, usually at a single time point during disease progression. While these lists have identified many novel genes that are altered during the disease process, they are unable to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 32 publications
(41 reference statements)
1
40
0
Order By: Relevance
“…We previously found that RNA expression of Wnt5a was increased in the knee joint tissue of DMM mice as OA developed 16 . Similar to our findings, a recent study also reported the presence of Wnt5a protein in articular cartilage of knee OA patients by IHC 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that RNA expression of Wnt5a was increased in the knee joint tissue of DMM mice as OA developed 16 . Similar to our findings, a recent study also reported the presence of Wnt5a protein in articular cartilage of knee OA patients by IHC 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Wnt5a expression was detected at increased levels in osteoarthritic tissues including cartilage, inflamed synovial membrane and acetabular labrum 1315 . We previously discovered Wnt5a as the most upregulated Wnt family member in a network analysis with time series microarray data from joints of mice with OA induced by destabilization of the medial meniscus (DMM) 16 . However, a role for Wnt5a in human chondrocytes or in cartilage degeneration during development of OA has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Using existing protein‐protein interaction data and an automated sub‐network searching tool (jActiveModules31) Loeser et al, defined a sub‐network associated with genes up‐regulated during the initial 4 weeks after destabilization of the medial meniscus (DMM) in a murine model, including heparin‐binding EGF‐like growth factor (HB‐EGF) 32. Olex et al33 developed this strategy further using time‐course gene expression data from a whole mouse joint model of OA to define perturbed sub‐networks. ECM‐receptor interaction and focal adhesion canonical pathways were enriched across all time‐points.…”
Section: Biology As a Systemmentioning
confidence: 99%
“…A number of contemporary studies have provided useful reference metabolomic and proteomic data from osteophytic cartilage,44 subchondral bone,45 and synovial fluid,46 or considered the role of metabolic pathways derived from transcriptomics data 33, 47. However, our understanding of the homeostatic control of metabolic fluxes in cartilage, bone, and synovial fluid is limited.…”
Section: Biology As a Systemmentioning
confidence: 99%
“…Building on the best practices used in different fields, MOPED integrates heterogeneous data into a unified public resource. The integration of multi-omics data can be essential for scientific discovery (Efron and Tibshirani, 2007;Huang, 2014;Huang et al, 2014;Olex et al, 2014), thus by providing a platform for multi-omics data, MOPED can act as a launching point for scientific discoveries.…”
Section: Introductionmentioning
confidence: 99%